If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + 3x = 2y Reorder the terms: 3x + 15y = 2y Solving 3x + 15y = 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15y' to each side of the equation. 3x + 15y + -15y = 2y + -15y Combine like terms: 15y + -15y = 0 3x + 0 = 2y + -15y 3x = 2y + -15y Combine like terms: 2y + -15y = -13y 3x = -13y Divide each side by '3'. x = -4.333333333y Simplifying x = -4.333333333y
| 9x-17=7x+11-x | | 3x+4y-2x=0 | | Cosx=-.7 | | 2-7=-11 | | 6x+9y-3=9 | | x+4-7= | | 2n=-146 | | 14+10=24 | | 12+x=8+4x | | -12=8+2 | | (16-2x)(8-2X)=20 | | p(a)=9/16 | | 4+6=-2 | | 500=100k | | -6(5x-3y+7)=0 | | p(a)=.25 | | -28=22-25x | | 8x-40/x(x-5) | | 4(d-9)+11=0 | | -3-9y=-13 | | 4x+11=14+15x | | p(a)=1 | | 36/42=18/c= | | .666+x=4 | | 5(4x-6)=(10x-15)2 | | 2z^3-12z^2+3z=0 | | a+0.5a= | | 8+3k=1 | | 18-3(5-2y)= | | 3x+c=b | | 3+4(5-2*6)+12(2+4)+1= | | 6-7(1a+1)=-3(2-6) |